Oxytocin Compared to Buccal Misoprostol for Induction of Labor after Term Prelabor Rupture of Membranes - Freret, Taylor S.; Chacón, Kelly M.; Bryant, Allison S.; Kaimal, Anjali J.; Clapp, Mark A. (American Journal of Perinatology, 2019)
Objective This study was aimed to determine if admission-to-delivery times vary between term nulliparous women with prelabor rupture of membranes (PROM) who initially receive oxytocin compared with buccal misoprostol for labor induction.Study Design This is a retrospective cohort of 130 term, nulliparous women with PROM and cervical dilation of ≤2 cm who underwent induction of labor with intravenous oxytocin or buccal misoprostol. The primary outcome was time from admission to delivery. Linear regressions with log transformation were used to estimate the effect of induction agent on time to delivery.Results Women receiving oxytocin had faster admission-to-delivery times than women receiving misoprostol (16.9 vs. 19.9 hours, p = 0.013). There were no significant differences in secondary outcomes between the groups. In the adjusted model, women who received misoprostol had a 22% longer time from admission to delivery (95% CI 5.0–42.0%) compared with women receiving oxytocin.Conclusion In term nulliparous patients with PROM, intravenous oxytocin is associated with faster admission-to-delivery times than buccal misoprostol.
Keywords: prelabor rupture of membrane; induction of labor; buccal misoprostol; oxytocin